Factors for nonadherence to first line art therapy in a cohort of Human Immunodeficiency Virus positive adult patients - H., Sivaranjani; Patel, Harsha V.; S., Meghana B. (International Journal of Advances in Medicine, 2019)
Background: Antiretroviral therapy is one of the reasons for falling trend of HIV epidemic at present. The clinical efficacy, toxicity and reasons for failure of first line ART is understudied. This study aimed to determine the frequency rates and reasons for discontinuation of first line ART in a cohort of HIV positive adult patients. Methods: Cross sectional study was conducted on 11,968 patients of HIV registered at Victoria Hospital ART centre from 2011 to 2017. Using a structured proforma, relevant information was collected from patients taking first line ART. Descriptive statistics was used for analysing the results obtained. Results: Total 11,968 HIV patients were registered at ART centre during our study period of which only 4,008 patients were taking ART among them, 167 patients were referred for initiation of 2nd line ART. After evaluation 28 were continued on First line,1 opted out, 20 were transferred out,1 discontinued treatment, 17 died, 14 were lost to follow up, 5 were excluded from the study and only 81 patients were started on second line ART. Failure rate of first line ART in our study was 2.02%. Immunological failure followed by clinical failure were the most common reasons for changeover in this study. Tuberculosis was the most common comorbid disease in this study. Conclusions: First line ART is very effective and well tolerated and has a low failure rate. Low CD4 count, anaemia, raised ALP, low albumin were among the factors associated with treatment failure. WHO staging did not correlate with the treatment failure, recommended routine viral load monitoring for assessing treatment failure.